A new type face-centered cubic zirconium phase in pure zirconium. (10th August 2021) - Yuan, Fusen; Li, Geping; Han, Fuzhou; Zhang, Yingdong; Muhammad, Ali; Guo, Wenbin; Ren, Jie; Liu, Chengze; Gu, Hengfei; Yuan, Gaihuan
Graphical abstract: Highlights: A distinctive new type γ phase was firstly reported in pure zirconium. The orientation relationship is: < 11 2 ¯ 0 > α ∥ < 1 ¯ 10 > γ and 0001 α ∥ 002 γ . α→γ phase transformation can be accomplished via expansion and slip. Abstract: So far, only two orientation relationships (OR) between hexagonal close-packed (HCP) (α phase) and face-centered cubic (FCC) structures in zirconium and titanium alloys have been reported. Here a new type FCC phase (named γ phase) with OR: < 11 2 ¯ 0 > α ∥ < 100 > γ and 0001 α ∥ 002 γ was observed for the first time in annealed pure zirconium by means of transmission electron microscopy (TEM) technique. The α→γ phase transformation can be accomplished via expansion along [ 1 1 ¯ 00 ] direction and slip of Shockley partial dislocation with 1 / 3 [ 1 1 ¯ 00 ] on (0001) basal planes.